Seminar Literasi Digital Bertema : Meningkatkan Ekonomi dan Menjaga Budaya di Era Digital - Nashrulloh, Muhammad Rikza; Yanti, Yanti; Riyandi, Fachrry Al-Fachrizzy; Nurodin, Azmi Miftah; Alinurdin, Rendi; Jipar, Muzaki Abdul; Faris, Salman Adam; Dzulkhomzah, Moh. Rival; Kifti, Jalaludin; Masripah, Ulpah; Alawiyah, Dini; Muttaqin, Iswan Nurul; Mubarok, Muhammad Imam Husni; Maulana, Moh. Alvin Apita; Akib, Yasir Al; Sidik, Ghimnastiar Moch; Nurhakim, Sultan Jabar; Rizki, Ikbal; Ramadhan, Tasya Shakila; Ridha, Muhamad Munna Ar; Oktaviany, Sindi; Fauzi, Sandi Muhtar (Jurnal PkM MIFTEK, 2023)
Globalization and the acceleration of technological advances have had such a significant impact in various fields. The presence of technology provides a new face for economic development and this becomes an opportunity and a big change for the system, process or economic actors themselves. Therefore it really needs counseling to help digitally literate people through digital literacy seminars with the theme Â«improving the economy and maintaining culture in the digital eraÂ» which will help, assist the community, for example in the use of common applications needed daily, the ethics of using technology wisely, maintaining culture in the digital era and so on, everything is explained in counseling on digital literacy.